Microcirculation in women with severe pre‐eclampsia and HELLP syndrome: a case–control study. (11th November 2013) - Cornette, J; Herzog, E; Buijs, EAB; Duvekot, JJ; Rizopoulos, D; Hop, WCJ; Tibboel, D; Steegers, EAP
<x xml:space="preserve">Abstract</x> Objective To compare microcirculatory perfusion in women with severe pre‐eclampsia against that in healthy pregnant women, and secondly in women with severe pre‐eclampsia with or without HELLP syndrome (haemolysis, elevated liver enzymes, and low platelets). Design Case–control study. Setting University Hospital Rotterdam, the Netherlands. Population Twenty‐three women with severe pre‐eclampsia and 23 healthy pregnant controls, matched for maternal and gestational age. Out of the 23 women with severe pre‐eclampsia, ten presented with HELLP syndrome. Methods Microcirculation was analysed sublingually by a non‐invasive sidestream dark‐field imaging device (SDF). Main outcome measures Perfused vessel density (PVD), microcirculatory flow index (MFI), and heterogeneity index (HI) were calculated for both small vessels (∅ < 20 μm; capillaries) and non‐small vessels (∅ > 20 μm; venules and arterioles). Results There were no significant differences between women with severe pre‐eclampsia and healthy controls. Women with pre‐eclampsia and HELLP syndrome showed a reduced PVD (P = 0.045), MFI (P = 0.008), and increased HI (P = 0.002) for small vessels, as compared with women with pre‐eclampsia but without HELLP syndrome. Conclusions Sidestream dark‐field is a novel, promising technique in obstetrics that permits the non‐invasive evaluation of microcirculation. We did not observe major differences in sublingual microcirculatory perfusion between women with severe pre‐eclampsia and healthy pregnant controls. In women with severe pre‐eclampsia, the presence of HELLP syndrome is characterised by impaired capillary perfusion.